Shadowy characters and fragmentary evidence: the search for early Christian groups and movements - Verheyden, Joseph; Nicklas, Tobias; Hernitscheck, Elisabeth (Wissenschaftliche Untersuchungen zum Neuen Testament, 2017)
The present volume contains the proceedings of an international colloquium that dealt with heavily fragmented texts and hypothetical sources, and with the "shadowy" characters and movements featured in such texts. These two aspects are combined here and studied to see how they have been handled in the history of research, what they reveal about the community or the group expressing itself through (or hiding behind) them, and to ascertain the role these documents and figures or groups should be given in reconstructing an overall picture of developments in the theology and religious life of early Christianity. The essays contribute to the writing of a critical history of researching these types of documents and movements